Conductive copper foil single-sided adhesive tape with high initial adhesion and high stripping force and preparation method thereof

By developing high-primary adhesive and high-peel conductive copper foil single-sided tape, the existing copper foil tape is solved, and the problems of softness and easy breakage, insufficient initial adhesive and adhesive strength, and insufficient aging resistance are achieved, and efficient electromagnetic shielding and long-term stable adhesion performance are achieved.

CN119662150APending Publication Date: 2025-03-21SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411829687.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing copper foil tape is soft and easy to break, with insufficient initial adhesion and adhesion force, which makes it difficult to meet the needs of high-speed mechanized production, and has insufficient aging resistance, which makes it easy to fall off on electronic components that are prone to heat generation, shortening service life.

Method used

A single-sided tape of conductive copper foil with high initial adhesive and high peel force is developed, using a copper foil layer, a conductive adhesive layer and a release film layer. The conductive adhesive layer is composed of acrylic adhesive liquid, tackifying resin, curing agent and conductive filler. By adjusting the formula and process, the conductive properties and aging resistance of the tape are improved.

Benefits of technology

It has achieved high initial adhesion, strong peeling force and good conductivity, and has good high-temperature adhesion and aging resistance. Its performance is better than that of commercially available single-sided adhesives, especially in high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662150A_ABST
    Figure CN119662150A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to a conductive copper foil single-sided adhesive tape with high initial adhesion and high stripping force and a preparation method thereof. The adhesive tape comprises a copper foil layer, a conductive adhesive layer is bonded on the lower surface of the copper foil layer, and a release film layer is bonded on the lower surface of the conductive adhesive layer. The high-performance glue is developed, the branched nickel powder is used for improving the conductivity of the adhesive tape, the dosage of the tackifying resin is adjusted, the conductive copper foil single-sided adhesive with high initial adhesion, high stripping force and certain aging resistance is obtained, and the conductive copper foil single-sided adhesive is remarkable in high-temperature and high-humidity resistance, long in service life, high in adhesion performance and sufficient in conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to a high initial adhesion and high peeling force conductive copper foil single-sided adhesive tape and a preparation method thereof. Background Art

[0002] With the popularization of consumer electronic products such as mobile phones, computers, and smart watches, and the promotion of 5G technology, consumer electronic products tend to be intelligent and thin, and the requirements for electronic product components are getting higher and higher. On the one hand, intelligence requires electronic components to be able to work under high-frequency electromagnetic waves. High-frequency electromagnetic waves seriously interfere with electronic components, so there are higher requirements for the shielding effectiveness of electromagnetic shielding materials.

[0003] On the other hand, the thinness and lightweight of consumer electronic products requires the lightweight size of electronic components, which limits the space for pasting electromagnetic shielding materials. The smaller bonding area places higher demands on the adhesion and shielding effectiveness of electromagnetic shielding materials, especially in the context of high-speed mechanized production. The smaller bonding pressure and shorter bonding time pose great challenges to the initial adhesion, bonding strength and conductivity of pressure-sensitive adhesives.

[0004] Bonding copper foil tape to electronic components can shield electromagnetic waves and prevent them from spreading outward and affecting the normal operation of electronic components. Copper foil, as a high-performance electromagnetic shielding material, is mostly used to prepare metal foil shielding tape. Copper foil itself has excellent electrical conductivity and can shield electromagnetic waves, and the conductive material of copper foil tape can also shield electromagnetic waves.

[0005] For example, the Chinese patent with publication number CN114774013A discloses a heat-resistant and moisture-resistant copper foil tape and a preparation method thereof, which comprises, from top to bottom, an electroplated oxide layer, a release layer, a conductive pressure-sensitive adhesive layer, a conductive paste layer, and a copper foil layer; the conductive pressure-sensitive adhesive layer is made of the following components in parts by weight: methyl methacrylate / ethylene carbonate / 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxaline 30-40 parts of ketone / vinyl trimethoxysilane / isopropenyl boric acid pinacol ester copolymer, 20-30 parts of copper powder, 10-20 parts of nickel powder, 20-30 parts of diluent, 3-5 parts of ethylene glycol dimethacrylate, 0.5-0.8 parts of initiator, 1-3 parts of aluminum chloride, and 0.8-1.5 parts of methacryloyl chloride; the heat-resistant and moisture-resistant copper foil tape prepared by the invention has remarkable high temperature and humidity resistance, long service life, strong adhesion performance, and sufficient conductivity.

[0006] However, including the above-mentioned patented products, the copper foil tapes currently sold on the market are relatively soft and easily damaged during use. In addition, the initial adhesion and bonding strength are insufficient, which is not conducive to high-speed mechanized production; the aging resistance is not good, and the copper foil tape will fall off after long-term use in heat-prone electronic components, greatly shortening the service life of the copper foil tape. Therefore, a conductive copper foil single-sided adhesive with high initial adhesion and high peeling force is needed, and it has certain aging resistance.

[0007] In order to solve the above problems, the present invention provides a high initial adhesion and high peeling force conductive copper foil single-sided tape and a preparation method thereof. Summary of the invention

[0008] The object of the present invention is to provide a conductive copper foil single-sided tape with high initial adhesion and high peeling force and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a high initial adhesion and high peeling force conductive copper foil single-sided tape, comprising a copper foil layer, a conductive adhesive layer bonded to the lower surface of the copper foil layer, and a release film layer bonded to the lower surface of the conductive adhesive layer;

[0010] The conductive adhesive layer includes the following substances by weight:

[0011] Acrylic adhesive 70-90 parts

[0012] 10-30 parts of tackifying resin

[0013] Curing agent 0.5-1.0 parts

[0014] Conductive filler 10-50 parts

[0015] Solution 50-100 parts.

[0016] More optimally, the thickness of the copper foil layer is 12-45um, the lower surface of the copper foil layer is a roughened matte surface, and convex points are evenly distributed on the surface; the acrylic adhesive is synthesized from acrylic monomers and acrylic functional monomers.

[0017] More optimally, the acrylate monomer is at least one of ethyl acrylate, butyl acrylate, acrylic acid, methyl acrylate, and isooctyl acrylate.

[0018] More optimally, the acrylic functional monomer is at least one of acrylamide, carboxymethyl acrylamide, and hydroxyethyl methacrylate.

[0019] More optimally, the initiator is at least one of benzoyl peroxide, dibenzoyl peroxide, azobisisobutyronitrile, diester of azobisisobutyrate, lauroyl peroxide, and tert-butyl perbenzoate.

[0020] More optimally, the solvent is at least one of ethyl acetate, butyl acetate and n-heptane.

[0021] More preferably, the tackifying resin is at least one of rosin resin, terpene resin or petroleum resin having a softening point between 70-160°C.

[0022] More optimally, the curing agent is one or both of an epoxy curing agent and an isocyanate curing agent.

[0023] More optimally, the conductive filler is a branched nickel powder, which has a chain structure composed of single particles connected to each other, and D50=17-22um.

[0024] The present invention also provides a method for preparing a high initial adhesion and high peeling force conductive copper foil single-sided adhesive tape, which is used for any of the above-mentioned high initial adhesion and high peeling force conductive copper foil single-sided adhesive tapes, comprising the following steps:

[0025] S1, taking a certain amount of acrylic acid isocyanate, butyl acrylate, vinyl acetate, acrylic acid, hydroxyethyl acrylate and ethyl acetate, mixing them and adding them into a four-necked reactor, adjusting the temperature to 55-75°C, adjusting the speed of the stirring paddle to 180rpm, stirring continuously, and introducing nitrogen. At this time, the solid content of the mixed monomers is 47%, and the total number of parts is 85;

[0026] S2, after nitrogen is introduced for 30-40 minutes, the temperature is kept stable at 65°C, a mixed solution of 0.01 parts of dibenzoyl peroxide, 0.01 parts of azobisisobutyronitrile, and 0.04 parts of ethyl acetate is added to the reactor, and the temperature is kept for 30-40 minutes. After continuous fine bubbles appear at the edge, the temperature is raised to 80-85°C;

[0027] At this time, add a mixed solution of 0.02 parts of dibenzoyl peroxide and 0.4 parts of ethyl acetate, maintain the temperature at 80-85°C, and stir at 180 rpm for 1 hour;

[0028] Then, 0.02 parts of dibenzoyl peroxide, 1.2 parts of vinyl acetate, and 0.4 parts of ethyl acetate were added, the temperature was maintained at 80-85°C, and stirring was continued at 180 rpm for 1 hour;

[0029] Then add 0.02 parts of dibenzoyl peroxide and 0.04 parts of ethyl acetate, keep the temperature at 80-85°C, and stir at 180rpm for 3 hours; nitrogen is continuously introduced during this process, then condensed and refluxed to 40°C, 10-20 parts of ethyl acetate are added, and cooled to room temperature. At this time, the mixed solid content of the glue is 40%, and the total number of parts is 100;

[0030] S3, add 3% conductive nickel powder by weight of the glue to the glue obtained in S2, disperse by ultrasonic for 5-10 minutes, add 5-10% resins with different softening points by weight of the glue, adjust the solid content of the solution to 15-25% by using ethyl acetate as solvent, stir at a speed of 600-1000rpm / min for 20-30min, add 1.0% epoxy resin curing agent and 0.5% isocyanate curing agent by weight of the glue, and stir at a speed of 600-1000rpm / min for 15-20min;

[0031] S4, using the scraper process, coated on the 50μm release film to form a 13±2μm dry adhesive, and bonded to the 35μm electrolytic copper rough surface, with a bonding pressure of 0.2MPa and a bonding speed of 5m / min. After aging at 48℃ for 24 hours, a single-sided conductive copper foil adhesive with a total thickness of 45±5μm was obtained.

[0032] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0033] (1) In the present invention, by developing high-performance glue, using branched nickel powder to improve the conductive properties of the tape, and adjusting the amount of tackifying resin, a conductive copper foil single-sided adhesive with high initial adhesion, high peeling force and certain aging resistance is obtained.

[0034] (2) In the present invention, acrylic pressure-sensitive adhesive is used, which reduces the cost, has a high production speed, a low curing temperature condition, and a low production line investment, thereby greatly reducing the production cost.

[0035] (3) In the present invention, the prepared tape has good adhesion to SUS at room temperature, can achieve rapid adhesion at room temperature, has good initial adhesion, peeling force and good electrical conductivity, and has good high-temperature adhesion and aging resistance.

[0036] (4) The heat-resistant and moisture-resistant copper foil tape disclosed in the present invention has remarkable high temperature and high humidity resistance, long service life, strong adhesion performance, and sufficient conductivity.

[0037] (5) The performance of the adhesive tape prepared by the present invention is superior to that of commercially available single-sided adhesive in all aspects, and the comprehensive conductive performance is improved several times, especially the vertical resistance, which is only 1 / 20 of that of commercially available single-sided adhesive; the peeling force is also stronger than that of commercially available single-sided adhesive, especially the peeling force after aging for 3 days, which is much stronger than that of commercially available single-sided adhesive; therefore, the adhesive tape prepared by the present invention is superior to commercially available single-sided adhesive in terms of high temperature and high humidity resistance, excellent adhesion performance, and conductive performance much stronger than that of commercially available single-sided adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0039] Figure 1 This is a schematic diagram of the structure of Example 1.

[0040] In the figure, 1, copper foil layer; 2, conductive adhesive layer; 3, release film layer. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The invention provides a method for preparing a conductive copper foil single-sided tape with high initial adhesion and high peeling force, and the specific steps are as follows.

[0043] 1. Preparation of glue synthesis:

[0044] Step 1: Preparation of mixed monomers

[0045] A mixed solvent (25-30 parts of acrylate isocyanate, 5-10 parts of butyl acrylate, 1-2 parts of vinyl acetate, 1-2 parts of acrylic acid, 0.05-0.1 parts of hydroxyethyl acrylate and 40-50 parts of ethyl acetate) is added to a four-necked reactor, the temperature is adjusted to 55-75°C, the speed of the stirring paddle is adjusted to 180 rpm for continuous stirring, and nitrogen is introduced. At this time, the solid content of the mixed monomers is about 47%, and the total number of parts is about 85 parts.

[0046] Step 2: Preparation of acrylic copolymer

[0047] Nitrogen was introduced for 30-40 minutes, and the temperature was kept stable at 65°C. A mixed solution of 0.01 parts of dibenzoyl peroxide, 0.01 parts of azobisisobutyronitrile, and 0.04 parts of ethyl acetate was added to the reactor, and the mixture was kept warm for 30-40 minutes. After continuous fine bubbles appeared on the edge, the temperature began to rise to 80-85°C; a mixed solution of 0.02 parts of dibenzoyl peroxide and 0.4 parts of ethyl acetate was added, the temperature was kept at 80-85°C, and stirring was continued at 180rpm for 1H; 0.02 parts of dibenzoyl peroxide, 1.2 parts of vinyl acetate, and 0.4 parts of ethyl acetate were added, the temperature was kept at 80-85°C, and stirring was continued at 180rpm for 1H; 0.02 parts of dibenzoyl peroxide and 0.04 parts of ethyl acetate were added, the temperature was kept at 80-85°C, and stirring was continued at 180rpm for 3H. During this process, nitrogen is continuously introduced, and then condensed and refluxed to 40° C., 10-20 parts of ethyl acetate are added, and cooled to room temperature. At this time, the mixed solid content of the glue is about 40%, and the total number of parts is 100 parts.

[0048] 2. Formulation design of high initial adhesion and high peeling adhesive

[0049] The present invention verifies the performance of the prepared tape through several examples, and each example selects polyacrylic acid adhesive (A) (B) (C) (D) (E) respectively, and the specific formula design is shown in Table 1.

[0050] Conductive nickel powder (D50 = 17-22 um) accounting for 3% of the mass of the glue was added to the adhesive of each embodiment, and ultrasonic dispersion was performed for 5-10 minutes. Resins (F) (G) with different softening points accounting for 5%-10% of the mass of the glue were added, and the solid content of the solution was adjusted to 15%-25% using ethyl acetate as a solvent. The mixture was stirred at a high speed (600-1000 rpm / min) for 20-30 minutes. An epoxy resin curing agent (H) accounting for 1.0% of the mass of the glue and 0.5% of an isocyanate curing agent (I) were added, and the mixture was stirred at a high speed (600-1000 rpm / min) for 15-20 minutes.

[0051] Table 1 Formula design table of each embodiment (mass ratio)

[0052] Product Name Adhesive Resin (F) Resin (G) Epoxy curing agent (H) Isocyanate curing agent (I) Conductive nickel powder Example 1 A 10 5 1 0.5 3 Example 2 B 10 5 1 0.5 3 Example 3 C 10 5 1 0.5 3 Example 4 D 10 5 1 0.5 3 Example 5 E 10 5 1 0.5 3 Example 6 E 10 5 0 0.5 3 Example 7 E 8 4 0 0.5 3 Example 8 E 7 3 0 0.5 3 Example 9 E 6 2 0 0.5 3

[0053] After obtaining the adhesive tapes prepared in each embodiment, experiments need to be conducted to test their performance.

[0054] 1. Performance test:

[0055] The conductive adhesive prepared in Example 1-12 was coated on a 50 μm release film to form a 13±2 μm dry adhesive, which was then laminated to the rough surface of 35 μm electrolytic copper using a laminating machine (laminating pressure 0.2 MPa, laminating speed 5 m / min). After aging at 48°C for 24 hours, a single-sided conductive copper foil adhesive with a total thickness of 45±5 μm was obtained, and its basic performance was tested.

[0056] (1) 180° peel strength test: Place the sample under test at 23±3℃ and 50±5%RH for 24h, cut three strips with a width of 25±1mm and a length of 300±20mm, and stick them parallel to the steel plate. Use an electric roller (weight 2kg) to roll back and forth on the test piece at a speed of 300mm / min under its own weight, and leave it for 20min.

[0057] Peel off the adhesive surface from the steel plate along the free end of the test piece, clamp the free end of the test piece and the steel plate on the upper and lower clamps respectively and keep them at the same level as the tensile testing machine, peel off the tape on the tensile testing machine at a speed of 300mm / min, and take the average value of the peeling force within the stroke of 50-150mm. Repeat the test 3 times and take the average value.

[0058] For the aging 180° peel strength, place the sample at 65℃ / 90%RH for 72 hours, then place the sample at 23±3℃, 50±5%RH for 24 hours, and then test it according to the above steps. For the 180° peel strength at 65℃ / 90%RH, place the sample at 65℃ / 90%RH for 20 minutes, and then test it according to the above steps.

[0059] (2) Probe initial adhesion: Place the sample to be tested at 23±3℃ and 50±5%RH for 24h, and cut 5 samples of 25mm*25mm with a cutting knife. Turn on the probe initial adhesion tester and use a 200g weight for calibration. Select the D2979 Test Method mode for testing, place the sample to be tested flat on the test fixture, and start the test. After the test, record the maximum value in the graph as the test value. Repeat the test 3 times and take the average value.

[0060] (3) Conductivity test: Place the sample under test at 23±3℃ and 50±5%RH for 2h, and cut the sample into 30mm*30m pieces with a cutter. Place the sample on the table with the surface to be tested facing up, place the horizontal resistance test fixture on the surface to be tested, press gently to make it fit completely with the sample, let it stand for 60s until the reading stabilizes, then record the horizontal resistance, repeat the test 3 times and take the average value; fit the surface to be tested of the sample flat with the vertical resistance test fixture (lower), place another vertical resistance test fixture (upper) on the other side of the test sample, let it stand for 60s until the reading stabilizes, then record the vertical resistance, repeat the test 3 times and take the average value.

[0061] After testing, the results obtained in each embodiment are shown in Table 2 and Table 3.

[0062] Table 2 Performance test results in Examples 1-5

[0063]

[0064] Examples 1-5 correspond to adhesives formed by different synthetic formulas. The same formula was scraped and tested to verify their peeling force, probe initial adhesion and conductive properties.

[0065] Examples 2, 3, 4, and 5 have good peeling force at room temperature, and their peeling force is greater than 2300 gf / in, indicating that they have good bonding performance to SUS at room temperature. However, Example 2 has average adhesion performance to SUS at 65°C / 90% RH, and its performance decays significantly after aging.

[0066] The peeling performance of Examples 3, 4, and 5 is good under the conditions of 65° C. / 90% RH and 65° C. / 90% RH for 3 days, indicating that they have good high-temperature adhesion and aging resistance.

[0067] Examples 1 and 5 have good initial adhesion performance at room temperature, indicating that they can achieve rapid adhesion at room temperature.

[0068] The conductive properties of Examples 1-5 are all relatively good, with horizontal resistance <20 mΩ / □ and vertical resistance <5 mΩ.

[0069] Combined with the above data comparison, the adhesive E used in Example 5 was further optimized to explore the effects of tackifying resin and curing agent on peel force and initial adhesion performance. At the same time, a commercially available conductive copper foil single-sided adhesive (from Polymer Science Inc.) was used as a comparative example to compare the performance of the tape prepared in the present invention.

[0070] Table 3 Performance test results of Examples 6-9 and Comparative Examples

[0071]

[0072] Examples 5 and 6 investigated the effect of epoxy curing agent on the performance of conductive copper foil single-sided adhesive. Compared with Example 6 without adding epoxy curing agent, the peeling force and probe initial adhesion at room temperature were improved to a certain extent on the basis of Example 5. Therefore, epoxy curing agent was no longer added in subsequent Examples 7, 8, and 9.

[0073] In Examples 7, 8, and 9, under the premise of a certain amount and type of curing agent, the effect of the amount of tackifying resin on the performance of the conductive copper foil single-sided adhesive was explored.

[0074] The experimental results show that as the amount of tackifying resin decreases, the peeling force and initial adhesion performance of the conductive copper foil single-sided adhesive can be improved to a certain extent, and its high-temperature peeling force and aging resistance are also improved. However, when the amount of resin is reduced to a certain value, the performance of the conductive copper foil single-sided adhesive does not continue to increase. This may be because the content of the tackifying resin is too low, which reduces the impact on the performance of the tape.

[0075] Compared with the commercially available single-sided adhesive (i.e., Comparative Example 1), it can be seen that the performance of the tape prepared by the present invention is superior to that of the commercially available single-sided adhesive in all aspects, and the comprehensive conductive performance is improved several times, especially the vertical resistance, which is only 1 / 20 of that of the commercially available single-sided adhesive; the peeling force is also stronger than that of the commercially available single-sided adhesive, especially the peeling force after aging for 3 days, which is much stronger than that of the commercially available single-sided adhesive; therefore, the high temperature and high humidity resistance of the tape prepared by the present invention is superior to that of the commercially available single-sided adhesive in all aspects, the adhesion performance is excellent, and the conductive performance is much stronger than that of the commercially available single-sided adhesive.

[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0077] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high initial adhesion and high peeling force conductive copper foil single-sided tape, characterized in that: It comprises a copper foil layer, a conductive adhesive layer is bonded to the lower surface of the copper foil layer, and a release film layer is bonded to the lower surface of the conductive adhesive layer; The conductive adhesive layer includes the following materials by weight: Acrylic adhesive 70-90 parts 10-30 parts of tackifying resin Curing agent 0.5-1.0 parts Conductive filler 10-50 parts Solution 50-100 parts.

2. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The copper foil layer has a thickness of 12-45um, and the lower surface of the copper foil layer is a roughened surface with convex points evenly distributed on the surface; the acrylic adhesive is synthesized from acrylic monomers and acrylic functional monomers.

3. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 2, characterized in that: The acrylic acid ester monomer is at least one of ethyl acrylate, butyl acrylate, acrylic acid, methyl acrylate and isooctyl acrylate.

4. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 2, characterized in that: The acrylic functional monomer is at least one of acrylamide, carboxymethyl acrylamide and hydroxyethyl methacrylate.

5. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The initiator is at least one of benzoyl peroxide, dibenzoyl peroxide, azobisisobutyronitrile, diester of azobisisobutyrate, lauroyl peroxide, and tert-butyl perbenzoate.

6. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The solvent is at least one of ethyl acetate, butyl acetate and n-heptane.

7. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The tackifying resin is at least one of rosin resin, terpene resin or petroleum resin with a softening point between 70-160°C.

8. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The curing agent is one or both of an epoxy curing agent and an isocyanate curing agent.

9. The conductive copper foil single-sided tape with high initial adhesion and high peeling force according to claim 1, characterized in that: The conductive filler is branched nickel powder, which is in the shape of a chain structure composed of single particles connected to each other, and D50=17-22um.

10. A method for preparing a high initial adhesion and high peeling force conductive copper foil single-sided tape, used for preparing any one of claims 1 to 9, characterized in that: The steps include: S1, taking a certain amount of acrylic acid isocyanate, butyl acrylate, vinyl acetate, acrylic acid, hydroxyethyl acrylate and ethyl acetate, mixing them and adding them into a four-necked reactor, adjusting the temperature to 55-75°C, adjusting the speed of the stirring paddle to 180rpm, stirring continuously, and introducing nitrogen. At this time, the solid content of the mixed monomers is 47%, and the total number of parts is 85; S2, after nitrogen is introduced for 30-40 minutes, the temperature is kept stable at 65°C, a mixed solution of 0.01 parts of dibenzoyl peroxide, 0.01 parts of azobisisobutyronitrile, and 0.04 parts of ethyl acetate is added to the reactor, and the temperature is kept for 30-40 minutes. After continuous fine bubbles appear at the edge, the temperature is raised to 80-85°C; At this time, add a mixed solution of 0.02 parts of dibenzoyl peroxide and 0.4 parts of ethyl acetate, maintain the temperature at 80-85°C, and stir at 180 rpm for 1 hour; Then, 0.02 parts of dibenzoyl peroxide, 1.2 parts of vinyl acetate, and 0.4 parts of ethyl acetate were added, the temperature was maintained at 80-85°C, and stirring was continued at 180 rpm for 1 hour; Then add 0.02 parts of dibenzoyl peroxide and 0.04 parts of ethyl acetate, keep the temperature at 80-85°C, and stir at 180rpm for 3 hours; nitrogen is continuously introduced during this process, then condensed and refluxed to 40°C, 10-20 parts of ethyl acetate are added, and cooled to room temperature. At this time, the mixed solid content of the glue is 40%, and the total number of parts is 100; S3, add 3% conductive nickel powder by weight of the glue to the glue obtained in S2, disperse by ultrasonic for 5-10 minutes, add 5-10% resins with different softening points by weight of the glue, adjust the solid content of the solution to 15-25% by using ethyl acetate as solvent, stir at a speed of 600-1000rpm / min for 20-30min, add 1.0% epoxy resin curing agent and 0.5% isocyanate curing agent by weight of the glue, and stir at a speed of 600-1000rpm / min for 15-20min; S4, using the scraper process, coated on the 50μm release film to form a 13±2μm dry adhesive, and bonded to the 35μm electrolytic copper rough surface, with a bonding pressure of 0.2MPa and a bonding speed of 5m / min. After aging at 48℃ for 24 hours, a single-sided conductive copper foil adhesive with a total thickness of 45±5μm was obtained.

Citation Information

Patent Citations

  • Temperature-resistant and moisture-resistant copper foil adhesive tape and preparation method thereof

    CN114774013A